ANALISIS KEMAMPUAN TEKNIK DASAR TIM BOLA VOLI SATPOL PP PROVINSI RIAU DI MASA PANDEMI COVID-19 - Ahmad Fadhil; Ni Putu Nita Wijayanti; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : The problem in this research is the decline in the appearance of athletes performing basic technical skills in playing volleyball, such as bottom passing, top passing, serving and smashing. The aim of this research was to determine the ability of basic volleyball techniques. The population in this study was the Satpol-PP volleyball club in Riau Province, with a total of 10 samples using a total sampling technique. The instruments in this research are pass tests, service tests and smash tests. The data obtained was analyzed using percentages. in the calculation of the description of this research data, namely in the service test there are 3 persons (30%) good category, 5 persons (50%) moderate category, 2 persons (20%) less category. In the successful test there were 6 people (60%) in the good category and 4 people (40%) in the good category. In the smash test they all (100%) have a good category. The conclusion of this research is that the ability of basic volleyball skills to pass a good category is equal to 60%..Keywords: Volleyball skills, Serving, Passing, Smash